Effects of OSA Surgery on Leptin and Metabolic Profiles. (December 2019) - Chin, Chien-Hung; Lin, Pei-Wen; Lin, Hsin-Ching; Friedman, Michael; Lin, Meng-Chih
Objectives: This study is designed to investigate the effects of obstructive sleep apnea/hypopnea syndrome (OSA) surgery on serum leptin levels and metabolic disturbances, both of which contribute to the risk of cardiovascular diseases. Study Design: Case series with planned data collection. Setting: Tertiary referral medical center. Subjects and Methods: A retrospective chart review of 101 consecutive patients with OSA who refused or failed conservative therapy and who then underwent upper airway surgery for OSA treatment was conducted. The personal medical history, anthropometric measurements, subjective symptoms, and objective polysomnographic parameters and fasting morning blood samples for leptin and metabolic biomarkers measurements were collected preoperatively and at a minimum of 3 months postoperatively. Results: Eighty patients with OSA (69 men and 11 women; mean [SD] age of 42.2 [10.2] years) with complete data were included in the final analysis. At least 3 months after surgery, serum leptin, low-density lipoprotein cholesterol (LDL-C), and triglyceride levels and the mean systolic blood pressure (SBP) (night and morning) significantly decreased. According to the classical definition of surgical success, 40 subjects had successful surgery and were categorized as surgical responders, and the other 40 patients who failed surgery were categorized as surgical nonresponders. Significant reductions in serum leptin, total cholesterol, LDL-C, and triglyceride levels and improvement of mean SBP (morning) occurred in surgical responders but not in nonresponders. Conclusions: Effective OSA surgery improves serum leptin, lipid profiles, and SBP. Further studies are needed to investigate the role of serial measurements of these biomarkers in monitoring surgical outcome of OSA treatment.